Ferromagnetic resonance driven by an ac current: a brief review - Wang, C.; Seinige, H.; Tsoi, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Excitation of ferromagnetic resonance (FMR) by an ac current has been observed in macroscopic ferromagneticfilms for decades and typically relies on the ac Oersted field of the current to drive magnetic moments into precession and classical rectification of ac signals to detect the resonance. Recently, current-driven ferromagneticresonances have attracted renewed attention with the discovery of the spin-transfer torque (STT) effect due toits potential applications in magnetic memory and microwave technologies. Here STT associated with the ac current is used to drive magnetodynamics on the nanoscale that enables FMR studies in sample volumes smaller by a factor of 1000 compared to conventional resonance techniques. In this paper, we briefly review the basics of STT–FMR technique and the results of various STT–FMR experiments.